Therapeutic Interventions for Diabetes Mellitus-associated Complications - Pradhan, Dharmendra; Sahu, Prafulla Kumar; Purohit, Sukumar; Ranajit, Santosh Kumar; Acharya, Biswajeet; Sangam, Shreya; Shrivastava, Amit Kumar (Current Diabetes Reviews, 2025)
BackgroundDiabetes Mellitus (DM) is an alarming health concern, affecting approximately 537 million people worldwide. As a leading cause of morbidity and mortality, DM demands a comprehensive understanding of its diverse pathophysiological mechanisms and disease progression.MethodsThis traditional review has consolidated literature on the pathogenesis of hyperglycemia, its progression into complications, and advances in optimal treatment strategies. The literature in the last two decades has been reviewed using several keywords, including “diabetes,” “diabetes-associated complications”, “novel therapeutic interventions for diabetes-associated diseases”, “phyto-extracts as antidiabetic drugs”, etc. in prominent databases, such as PubMed, Scopus, Google Scholar, Web of Science, and ClinicalTrials.gov.ResultsWe have discussed macrovascular and microvascular complications, such as atherosclerosis, cardiovascular disease, Peripheral Arterial Disease (PAD), stroke, diabetic nephropathy, retinopathy, and neuropathy, as well as various pharmacological and non-pharmacological interventions that are currently available for the management of DM. We have also focused on the potential of natural products in targeting molecular mechanisms involved in carbohydrate metabolism, insulin production, repair of pancreatic cells, and reduction of oxidative stress, thereby contributing to their antidiabetic activity. Additionally, novel therapeutic approaches, like genetic, stem cell, and immunomodulatory therapies, have been explored. We have also discussed the benefits and limitations of each intervention, emerging research and technologies, and precision medicine interventions.ConclusionThis review has emphasized the need for an improved understanding of these advancements, which is essential to enhance clinicians' ability to identify the most effective therapeutic interventions.
Keywords: therapeutic interventions